Experimental investigation of emission characteristics of diesel gasoline mixture containing n-butanol - S, Gopalakrishnan; A, Srinivaas (International Journal of Engineering and Technology, 2018)
Emissions have become an important parameter, playing an extensive role in the selection of engines. To find out the alternatives for petroleum based fuels owing to their continuous depletion and the increase in emission rates, research works are being carried out continuously. The prime objective of this work is to study the effects butanol additive to the diesel-gasoline mixture fuelled to a CI engine. The operation is carried out by mixing butanol with diesel-4% gasoline mixture at different proportions and the mixtures are used to run a single cylinder APEX 240PE kirloskar make engine at constant speed under a series of load conditions. The performance characteristics of the fuel mixture used is obtained and the concentration of emissions present in the exhaust has been determined using an Emission Analyzer. The mixture can be used as an alternative fuel in diesel engines, thereby producing reduced emission rates.